(untitled) (Antologia di Diritto Pubblico, 2026)
This paper re-examines Giannini’s fundamental contribution to studies on the interpretation of administrative acts and criticises the paradigm of borrowing the criteria referred to in Articles 1362-1371 of the Italian Civil Code, on which case law has been fossilised for over a century, highlighting how it lacks a solid foundation and is a source of contradictions and uncertainties.